Phytochemical Profile Screening and Selected Bioactivity of Myrtus communis Berries Extracts Obtained from Ultrasound-Assisted and Supercritical Fluid Extraction - Ilir Mërtiri; Gigi Coman; Mihaela Cotârlet; Mihaela Turturică; Nicoleta Balan; Gabriela Râpeanu; Nicoleta Stănciuc; Liliana Mihalcea (Separations)
This research paper investigates the phytochemical profile, antioxidant activity, antidiabetic potential, and antibacterial activity of Myrtus communis berries. Two extraction methods were employed to obtain the extracts: solid–liquid ultrasound-assisted extraction (UAE) and supercritical fluid extraction (SFE). The extracts were characterized using spectrophotometric methods and Reversed-Phase High-Performance Liquid Chromatography (RP-HPLC). The UAE extract exhibited higher total flavonoid and anthocyanin content, while the SFE extract prevailed in total phenolic content and antioxidant activity in the DPPH radical screening assay. RP-HPLC characterization identified and quantified several polyphenolic compounds. In the UAE extract, epigallocatechin was found in a concentration of 2656.24 ± 28.15 µg/g dry weight (DW). In the SFE extract, cafestol was the identified compound with the highest content at a level of 29.65 ± 0.03 µg/g DW. Both extracts contained several anthocyanin compounds, including cyanidin 3-O-glucoside chloride, cyanidin-3-O-rutinoside chloride, malvidin-3-O-glucoside chloride, pelargonidin 3-O-glucoside chloride, peonidin 3-O-glucoside chloride, and peonidin-3-O-rutinoside chloride. The antidiabetic potential was evaluated in vitro by measuring the inhibition of α-amylase from porcine pancreas (type I-A). The results highlighted the ability of myrtle berry extracts to inhibit α-amylase enzymatic activity, suggesting its potential as an alternative for controlling postprandial hyperglycemia. The UAE extract showed the lowest IC50 value among the two extracts, with an average of 8.37 ± 0.52 µg/mL DW. The antibacterial activity of the extracts was assessed in vitro against Bacillus spp., Escherichia coli, and Staphylococcus aureus using the disk diffusion method. Both myrtle berry extracts exhibited similar antibacterial activity against the tested bacterial strains. The results support further investigation of myrtle berries extracts as a potential ingredient in functional food formulation, particularly due to its antioxidant, antidiabetic, and antibacterial properties.